Analysis of The Influence of Pepper Plantations on Economic Growth Bangka Belitung Islands Province - Muhammad Gilang Ramadhan; Apriyansyah, Muhammad; Radensyah, Muhamad; Oktavia, Shela; Lestari, Nurul; Istiqomah, Fadilla Nurul; Iliana (Fakultas Ekonomi dan Bisnis, Universitas Bangka Belitung, 2024)
With abundant natural resources, Bangka Belitung Province is one of many provinces in Indonesia with a developing economic sector. One of the influences is white pepper, where the aim of this research is to examine the development of pepper production on the economy of Bangka Belitung. With a qualitative descriptive method using note-taking techniques and library techniques to accumulate data. The object of this research is pepper. In particular, in the Bangka Belitung Islands, pepper is known by the nickname sahang by the local community. Bangka Belitung pepper has a level of spiciness that exceeds the standards of other regions and a distinctive smell, namely the strong smell of essential oils. Based on the data obtained. From the results of this research, the Bangka Belitung Islands experience unstable developments in the pepper plantation sector every year, where production experiences significant increases and decreases.